Classification of Public Open Spaces Based on Form, Function, and Spatial Context Anisatur - Anisatur Robi’ah; Respati Wikantiyoso; Erlina Laksmiani Wahjutami (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Public Open Spaces (POS) play a crucial role in supporting environmental sustainability, quality of life, and socio-economic dynamics in urban areas. However, existing classifications of POS in the literature still exhibit considerable conceptual and methodological variation, indicating the need for a more structured synthesis. This study aims to identify and synthesize POS classifications based on form, function, and spatial context, and to determine the most dominant POS types over the last 13 years. The research employs a narrative literature review of 29 selected articles published between 2012 and 2025. Data were collected using Publish or Perish and the Google Scholar database, and screened according to specific inclusion criteria. The synthesis reveals that Parks/Gardens, Linear Spaces, Squares/Plazas, and Courtyards represent the primary POS forms; green, grey, and green/grey categories reflect surface-type variations; and recreational, ecological, and social functions emerge as the most dominant, alongside structural and economic functions. Spatially, studies are predominantly focused on urban areas, while peri-urban and rural contexts exhibit more transitional and organic spatial characteristics. This synthesis highlights the importance of holistic, context-based typological approaches in designing inclusive, multifunctional, and sustainable POS. The findings provide a theoretical foundation and practical guidance for planning and managing public open spaces across diverse spatial settings.